PENGEMBANGAN KONTEN PEMBELAJARAN MULTIMEDIA DIGITAL MINI SERVER LENTERA - Ganefri Ganefri; Febri Prasetya; Fadhli Ranuharja; Bayu Ramadhani Fajri; Agariadne Dwinggo Samala (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Educational problems in the 3T area (Disadvantaged, Frontier, and Outermost) areas, apart from teaching staff, such as shortage of teaching staff, low qualifications, low competence and mismatches between educational qualifications and fields being managed (mismatched) are also problems of inadequate telecommunications. network facilities, especially internet networks. Lentera (Source of Learning Materials for Remote Areas) is an innovative product in digital learning based on mobile learning applications that can be used without having to be connected to the internet (offline). The learning content is designed in the form of Whiteboard Animation-based learning multimedia or whiteboard animation. Learning content is uploaded to the mini server. The mini server called Lentera can be accessed by teachers and students using smartphones offline or does not require an internet network. The development of digital multimedia learning content with a mini server called Lentera aims to develop innovative digital learning media to support teachers and students who experience difficulties in internet networks to carry out digital learning in the 3T area. The method used in the construction of this mini server is the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The lantern as a blackboard animation learning medium is very feasible (valid) to be used in learning with an average validation value of 94.87%.